OSCILLATION PROPERTIES OF SOLUTIONS TO CONFORMABLE FRACTIONAL DELAY DIFFERENTIAL SYSTEMS - M. Deepa; M. Sathish Kumar; K. Karuppiah; S. Abhirami (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
This article examines the oscillation of solutions to a particular class of conformable fractional nonlinear delay differential systems of order α and 0<α≤1. By employing the equivalence transformation and the associated Riccati substitution technique, we are able to produce some new necessary conditions for the oscillation of all of the solutions of the differential system. Several results reported are extended, unified, and improved over established results. Two examples are provided to show the importance of the main results.